Improvement of international technology transfer rules in the european union through the prism of sustainable development policy - Pohorielova, Yuliia; Bakalinska, Olga; Shvydka, Tetiana; Vaksman, Rehina; Ostapenko, Iuliia (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the compliance of existing regulatory approaches to technology identification with the purpose of the EU sustainable development policy. It has been established that the effectiveness of the European Union’s sustainable development policy directly depends on the number of previously implemented technologies. It has been proven that such a dependence is both organizational and economic in nature. It has been determined that existing approaches to technology identification are not unified with the requirements of sustainable development policy. It has been proven that existing regulatory structures for defining technology do not contain restrictive means and therefore cannot be used within the framework of the European Union’s sustainable development policy. The feasibility of introducing a special type of key technologies into EU regulations that can be used as a restrictive means to achieve sustainable development goals has been substantiated. A definition of key technology has been formed as one that is capable of contributing to the achievement of sustainable development goals in the EU. It has been proposed to give priority to key technologies for use and apply support and incentive measures to them. Proposals have been formulated to amend the provisions of such international treaties and agreements as the TRIPS Agreement, WIPO recommendations, UNCTAD recommendations, and the Horizon Europe Framework Program. The study is aimed at forming general theoretical principles for improving the essence of the methods for identifying technology transfer for the purposes of sustainable development. The practical significance of the study results is that the results could be used in the formation of international regulatory acts, recommendations of international institutions, acts of national legislation, and serve as the basis for further scientific research on these issues